Systemic interferon type I and type II signatures in primary Sjögren's syndrome reveal differences in biological disease activity. (20th February 2018) - Bodewes, Iris L A; Al-Ali, Shereen; van Helden-Meeuwsen, Cornelia G; Maria, Naomi I; Tarn, Jessica; Lendrem, Dennis W; Schreurs, Marco W J; Steenwijk, Eline C; van Daele, Paul L A; Both, Tim; Bowman, Simon J; Griffiths, Bridget; et al.
Abstract: Objective: To assess the relationships between systemic IFN type I (IFN-I) and II (IFN-II) activity and disease manifestations in primary SS (pSS). Methods: RT-PCR of multiple IFN-induced genes followed by principal component analysis of whole blood RNA of 50 pSS patients was used to identify indicator genes of systemic IFN-I and IFN-II activities. Systemic IFN activation levels were analysed in two independent European cohorts ( n = 86 and 55, respectively) and their relationships with clinical features were analysed. Results: Three groups could be stratified according to systemic IFN activity: IFN inactive (19–47%), IFN-I (53–81%) and IFN-I + II (35–55%). No patient had isolated IFN-II activation. IgG levels were highest in patients with IFN-I + II, followed by IFN-I and IFN inactive patients. The prevalence of anti-SSA and anti-SSB was higher among those with IFN activation. There was no difference in total-EULAR SS Disease Activity Index (ESSDAI) or ClinESSDAI between the three subject groups. For individual ESSDAI domains, only the biological domain scores differed between the three groups (higher among the IFN active groups). For patient reported outcomes, there were no differences in EULAR Sjögren's syndrome patient reported index (ESSPRI), fatigue or dryness between groups, but pain scores were lower in the IFN active groups. Systemic IFN-I but not IFN-I + II activity appeared to be relatively stable over time. Conclusions: Systemic IFN activation is associated with higher activity only in the ESSDAI biological domain but not in other domains or the total score. Our data raise the possibility that the ESSDAI biological domain score may be a more sensitive endpoint for trials targeting either IFN pathway.